A multicenter, randomized, double-blind, placebo-controlled phase 3 study of Socazolimab or placebo combined with carboplatin and etoposide in the first-line treatment of extensive-stage small cell lung cancer - Zhiwei Chen; Jianhua Chen; Dingzhi Huang; Wei Zhang; Lin Wu; Tienan Yi; Qiming Wang; Liang Han; Liping Tan; Yinyin Li; Zhihong Zhang; Na Li; et al. (Signal Transduction and Targeted Therapy)
Abstract This is a randomized, double-blind, placebo-controlled phase 3 clinical trial (ClinicalTrials.gov, NCT04878016) conducted in 54 hospitals in China. Adults who were histologically diagnosed and never treated for extensive-stage small cell lung cancer (ES-SCLC) were enrolled. Eligible Patients were randomly assigned (1:1) to receive four cycles (21 days as one cycle) of intravenous carboplatin (area under the curve of 5 mg/mL per min, day 1 of each cycle) and etoposide (100 mg/m² of body-surface area, on days 1–3 of each cycle) with either socazolimab (5 mg/kg, day 1 of each cycle) or matching placebo, following maintenance therapy with socazolimab or placebo. From July 15, 2021, to May 12, 2022, 498 eligible patients were randomly assigned to receive socazolimab (250 patients) or placebo (248 patients) combined with chemotherapy. As of October 13, 2023, patients treated with socazolimab presented significant overall survival (OS) benefit (13.90 months) compared with the placebo plus EC group (11.58 months) (hazard ratio for death, 0.799; 95% CI, 0.652–0.979; p = 0.0158). The median progression free survival (PFS) was 5.55 months in the socazolimab plus EC group, prolonging disease progression or death by nearly 1.2 months (5.55 months vs 4.37 months, hazard ratio for progression or death, 0.569; 95% CI, 0.457–0.708; p < 0.0001). 200 (80.3%) patients in the socazolimab plus EC group experienced ≥ grade 3 treatment-related adverse events and 187 (75.7%) patients occurred in the placebo plus EC group. Socazolimab combined with standard EC regimen chemotherapy for first-line treatment of ES-SCLC significantly prolonged overall survival and did not increase the safety risk of treatment.